The Case Against Intervention - Chee-Heong Quah (UJ Press, 2023)
The Case Against Intervention - the fourth venture of the author Quah, Chee Heong, dwells upon contemporary social and economic issues. His previous books Optimal Currency Areas in East Asia, Eccentric Views on Money and Banking, and Austrian Economics in One Lesson lay stress on money, banking, and economics. This title concentrates on societal issues that currently define and affect our day-to-day lives which would certainly complement the curricula at colleges and universities. The objective of this work is to break the status quo and defy the fallacious reasoning in mainstream thinking, as Ronald Reagan once said, "Government is not the solution to our problem, government is the problem.
Keywords: 330; intervention; economics; government; trade; the state; politics; security; economic well-being; healthcare; discrimination; intrinsic market system